PENGARUH ASIMETRI INFORMASI DAN KEPEMILIKAN MANAJERIAL PADA PRAKTEK MANAJAMEN LABA - Andika, Sendhi; Sukartha, I Made (E-Jurnal Akuntansi, 2015)
Earnings management is a condition in which the management to intervene in the process of preparation of financial statements for external parties so as to flatten, raise, and lower profits. Earnings management occurs when using certain decisions in the management of financial reporting and the preparation of transactions that change the financial statements intended to mislead the stakeholders about the company's economic performance conditions. This study aimed to determine the effect of information asymmetry and managerial ownership on earnings management practices companies listed on the Stock Exchange. The data in this study were obtained from the manufacturing company's financial statements. The population in this study consisted of 134 companies listed on the Stock Exchange 2011-2013. Sampling using nonprobability sampling method is purposive sampling. The number of sample firms that meet the criteria are 26 manufacturing companies. Data analysis method used is multiple linear regression analysis. Based on the analysis and hypothesis testing can be concluded that the positive effect of information asymmetry on earnings management practices, while the negative effect of managerial ownership on earnings management practices.
Keywords: Earning Management, Information Asymmetry, Managerial Ownership